Photodissociation of bromine-substituted nitroimidazole radiosensitizers - Pihlava Lassi; Berholts Marta; Niskanen Johannes; Vladyka Anton; Kooser Kuno; Stråhlman Christian; Eng-Johnsson Per; Kivimäki Antti; Kukk Edwin (Royal Society of Chemistry, 2025)
Heavy elements and some nitroimidazoles both exhibit radiosensitizing properties through different mechanisms. In an effort to see how the overall radiosensitivity might be affected when the two radiosensitizers are combined in the same molecule, we studied the gas-phase photodissociation of two brominated nitroimidazoles and a bromine-free reference sample. Synchrotron radiation was employed to initiate the photodynamics and energy-resolved multiparticle coincidence spectroscopy was used to study the ensuing dissociation. We observed the brominated samples releasing high amounts of potentially radiosensitizing fragments upon dissociation. Since bromination also increases the likelihood of the drug molecule being ionised per a given X-ray dose, we conclude that heavy-element substitution of nitroimidazoles appears to be a viable path towards new, potent radiosensitizer drugs.